Single Parents and Communication Patterns in Post-Migrant Families: Insights from Resapombo Village - Ariel Rizky Putra Hartono; Nobertus Ribut Santoso (ULTIMA Comm, 2025)
This research aims to identify and analyze the communication patterns of single parents in post-migrant families in Resapombo Village, Doko District, Blitar Regency. The study employs a qualitative method, utilizing in-depth interview techniques for data collection. Three informants participated in this study, consisting of one father and three mothers, all of whom are single parents from post-migrant families. The findings reveal that the communication patterns of single parents in these families exhibit high levels of conversation and conformity dimensions, indicating a consensual family type with an authoritative parenting style. These parents engage in open dialogues with their children, encouraging discussions while also emphasizing the importance of family values and norms. The authoritative parenting style observed reflects a balance between responsiveness and demandingness, where single parents maintain control while nurturing their children's independence. This study provides valuable insights into the dynamics of communication within post-migrant families, highlighting the unique challenges and adaptations faced by single parents. Understanding these patterns is crucial for developing support systems and interventions tailored to the needs of single-parent post-migrant families. The results of this study contribute to the broader discourse on family communication, especially in the context of migration and its impact on family structures. Future research should explore the long-term effects of these communication patterns on children's development and well-being in post-migrant settings, as well as the role of community support in enhancing family resilience.